Contribution of Major Food Companies and Their Products to Household Dietary Sodium Purchases in Australia. (29th May 2020) - Coyle, Daisy; Shahid, Maria; Dunford, Elizabeth; Mhurchu, Cliona Ni; Mckee, Sarah; Santos, Myla; Popkin, Barry; Trieu, Kathy; Marklund, Matti; Taylor, Fraser; Neal, Bruce; Wu, Jason H Y
Abstract: Objectives: To support the work of the Australian federal governments proposed sodium reformulation targets, this study sought to identify the relative contribution that different food companies and their products make to household sodium purchases in Australia. We also examined differences in household sodium purchases from packaged foods and beverages by income level. Methods: We used one year of grocery purchase data from a nationally representative consumer panel of Australian households who reported their grocery purchases (the Nielsen Homescan panel), combined with a packaged food and beverage database (FoodSwitch) that contains brand- and product-specific sodium information. Outcome measures were sodium purchases per capita (mg/day), sodium density (mg/1000 kcal), and purchase-weighted sodium content (mg/100 g). The top food companies and food categories were ranked according to their contribution to household sodium purchases. Per capita sodium purchases was estimated in household income strata. All analyses were modeled to the Australian population in 2018 using sample weights. Results: Sodium data were available from 7188 households who purchased 26, 728 unique products and, in total, just under 7.5 million units of foods and beverages. The total sodium acquired from packaged foods and beverages was 1443 mg/day per capita. Out of 1329 food companies, the top 10 accounted for 58% of all sodium purchased from packaged foods and beverages. The top three companies were grocery food retailers each contributing 12–15% of sodium purchases from sales of their private label products, particularly processed meat, cheese and bread. Out of the 67 food categories, the top 10 accounted for 73% of sodium purchased, driven by purchases of processed meat (14%), bread (12%) and sauces (11%). Low-income Australian households purchased substantially more sodium from packaged products than high-income households per capita (220 mg/d, 95% CI: 132–307 mg/d, P  < 0.001). Conclusions: A small number of food companies and food categories account for the majority of dietary sodium purchased by Australian households. There is an opportunity for governments to prioritize engagement and incentivize key companies and food categories to deliver a large reduction in sodium intake and reduce cardiovascular disease. Funding Sources: National Health and Medical Research Council.